Domain-Specificity of Creativity: A Study on the Relationship Between Visual Creativity and Visual Mental Imagery - Palmiero, Massimiliano; Nori, Raffaella; Aloisi, Vincenzo; Ferrara, Martina; Piccardi, Laura (Frontiers in Psychology, 2015)
Creativity refers to the capability to catch original and valuable ideas and solutions. It involves different processes. In this study the extent to which visual creativity is related to cognitive processes underlying visual mental imagery was investigated. Fifty college students (25 women) carried out: the Creative Synthesis Task, which measures the ability to produce creative objects belonging to a given category (originality, synthesis and transformation scores of pre-inventive forms, and originality and practicality scores of inventions were computed); an adaptation of Clark’s Drawing Ability Test, which measures the ability to produce actual creative artworks (graphic ability, aesthetic and creativity scores of drawings were assessed) and three mental imagery tasks that investigate the three main cognitive processes involved in visual mental imagery: generation, inspection and transformation. Vividness of imagery and verbalizer-visualizer cognitive style were also measured using questionnaires. Correlation analysis revealed that all measures of the creativity tasks positively correlated with the image transformation imagery ability; practicality of inventions negatively correlated with vividness of imagery; originality of inventions positively correlated with the visualization cognitive style. However, regression analysis confirmed the predictive role of the transformation imagery ability only for the originality score of inventions and for the graphic ability and aesthetic scores of artistic drawings; on the other hand, the visualization cognitive style predicted the originality of inventions, whereas the vividness of imagery predicted practicality of inventions. These results are consistent with the notion that visual creativity is domain- and task-specific.